Wastewater treatment plant performance evaluation using artificial neural network model - Mustapha, Mujeli; Mohammed Saedi, Jami, Dr.; Nassereldeen, Ahmed Kabbashi, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.